SURFACE ROUGHNESS IMPROVEMENT OF POLYAMIDE RESIN DENTURE AFTER SOAKING IN 50% CINNAMON (Cinnamon burmanii) SOLUTION - Rheni Safira Isnaeni; Zwista Yulia Dewi; Muhammad Hamzah Rahmatullah (Journal of Health and Dental Sciences, 2021)
Polyamide resin is widely used in dentistry as a denture base material. Cinnamon burmanii has been proven to have antibacterial and antifungal substances. Therefore, it is the potential to be used as a nature denture cleanser. This study aimed to examine the effect of soaking 50% cinnamon extract solution on the surface roughness of polyamide resin. This study used 16 polyamide resin samples soaked in 50% cinnamon extract solution and 16 samples soaked in distilled water as the control group. It examined the surface roughness before and after immersion for four days and seven days. Data were analyzed using paired T-test and independent T-test. The results showed a significant difference in the surface roughness of polyamide resin before and after immersion in cinnamon solution for four days and seven days. The surface roughness change is due to the polyphenol's reaction on the polyamide resin surface, which has destroyed the polymer chain of polyamide resin. DOI : 10.54052/jhds.v1n2.p165-174